Zinc/CaMK II Associated-Mitophagy Signaling Contributed to Hippocampal Mossy Fiber Sprouting and Cognitive Deficits Following Neonatal Seizures and Its Regulation by Chronic Leptin Treatment - Li, Li-li; Jin, Mei-fang; Ni, Hong (Frontiers in Neurology, 2018)
The role of leptin in the pathogenesis of epilepsy is getting more and more attention in clinical and basic research. Although there are data indicating neuroprotective effects of elevated serum/brain leptin levels following acute seizures, no study to date has dealt with the impact of chronic leptin treatment on long-term brain injury following developmental seizures. The aim of this study was to evaluate whether chronic leptin treatment may have neuroprotective effects on cognitive and hippocampal mossy fiber sprouting following flurothyl-induced recurrent neonatal seizures and whether these effects are mediated by the zinc/CaMKII-associated mitophagy signaling pathway. Forty Sprague-Dawley rats (postnatal day 6, P6) were randomly assigned into two groups: neonatal seizure group and control group. At P13, they were further divided into control group, seizure group (RS), control + leptin (leptin, i.p., 2 mg/kg/day for 10 days), seizure+leptin group (RS+Leptin, 2mg/kg/day, i.p., for 10 consecutive days). Morris water maze test was performed during P27-P32. Subsequently, Timm staining and Western blotting were used to detect the mossy fiber sprouting and protein levels in hippocampus. Flurothyl-induced seizures (RS group) significantly down-regulated mitophagy markers PINK, Drp1, PHB, and memory marker CaMK II alpha while up-regulating zinc transporters ZnT3, ZnT4, ZIP7, and autophagy execution molecular cathepsin-E, which were paralleled with hippocampal aberrant mossy fiber sprouting and cognitive dysfunction. However, these changes were restored by chronic leptin treatment (RS+Leptin group). The results showed that leptin had neuroprotective effect on hippocampal pathological damage and cognitive deficits induced by neonatal seizures and suggested that Zinc/CaMK II associated-mitophagy signaling pathway in hippocampus may be a new target of leptin's neuroprotection, with potential value of translational medicine.